Factor analysis of the role of physicians and its associated factors for encompassing patients with suspected tuberculosis in Surabaya City - Rosita D. Yuliandari; Chatarina Umbul Wahyuni; Fariani Syahrul; Hari B. Notobroto; Mochammad B. Qomaruddin; Soedarsono Soedarsono (AOSIS, 2023)
Background: Indonesia remains the highest tuberculosis morbidity rate, 9.6 million globally. Limited detection and surveillance of suspected tuberculosis need to be enhanced. Objective: This study aims to investigate the factors that influence the role of Physicians in screening for suspected tuberculosis. Materials and Methods: a case-control study with secondary datasets of 132 physicians. The analysis used is simple logistic regression and multiple logistic regressions. Results: out of 132, only 34 physicians (25.7%) have an active role; meanwhile, 98 physicians (74.3%) did not participate in assisting suspected tuberculosis. Almost 73% of physicians have not received additional training in tuberculosis management. The physicians contributed 19.1% to the total discovery of tuberculosis suspected in Surabaya. Age, years of working, and the number of patient visits were associated with the role of physicians in tuberculosis screening (OR of 3.809, 1.112, and 3.057). Conclusions: based on 5 variables that qualify for multivariate analysis, three factors greatly influence the physicians' role in screening tuberculosis suspected, including age, number of patient visits, and years of working.